Chapter 6 Collaborative Robots - kumar, atal anil (Taylor & Francis, 2024)
Collaborative robots or cobots are one of the core technologies of Industry 4.0 as they can collaborate with the workers to perform tasks. This feature of cobots makes them an alternative to conventional industrial robots as they are more flexible, light weight and more intuitive. Several industries have started using them in their production line due to the increasing need to move towards incorporating Industry 4.0 technologies. However, its implementation in small and medium-sized enterprises (SMEs) is still at an early stage. This chapter focuses on the challenges for SMEs when introducing cobots in their manufacturing line. Understanding these challenges will help the reader in identifying the right applications and approaches for implementing cobots for their manufacturing line.